The Effectiveness of Selected Radiosurgery Devices on Cancer Tumors and Arteriovenous Malformations: A Systematic Review - Majid Davari; Monireh Afzali; Mansoure Sabbagh-; Zahra Sharif; Fatemeh Hadizadeh; Parisa Mirmoghtadaee; Seyyed Mostafa Hoseini; Asghar Bakrani; Farzaneh Kolahdouzan (Tehran University of Medical Sciences, 2019)
Background: There are several types of radiotherapy devices available for the treatment of cancer tumors. The present study aimed to evaluate the effectiveness of selected radiosurgery devices on the treatment of cancer tumors and Arteriovenous Malformations (AVM). Methods: The evaluation was performed in two steps; First, evaluating the effectiveness of CyberKnife, Gamma knife and Linear Accelerator (Linac) on various biological systems. Then, we compered the effectiveness of devices with each other. A systematic review was conducted in MEDLINE, EMBASE, CRD, NHSEED and Cochrane library databases. The search strategy was limited to clinical trials with less than 5 treatment sessions. All searches were conducted on December 21, 2014. Results: In total, 81 studies have been included to the review. Based on the obtained results of comparison between the reported percentages of local control rate, the safety and accuracy of CyberKnife and linac are higher than Gamma Knife. Conclusion: Our findings suggested that CyberKnife is not only more effective to cover various types of tumors in the whole body, but also is safer and easier to use for various tumors, as well as AVM treatment.